DINAMIKA EKSISTENSI TRAKTAT MULTILATERAL DAN BILATERAL TERHADAP PERLINDUNGAN HAK-HAK EKONOMI DI INDONESIA: TINJAUAN KEPUSTAKAAN PERJANJIAN-PERJANJIAN PERDAGANGAN BEBAS - Gunawan Widjaja; Januar Agung Saputera (JOURNAL OF LAW AND NATION, 2025)
This study examines the dynamics of the existence of multilateral and bilateral treaties in the context of economic rights protection in Indonesia through a literature review approach. The main focus of the study is how these two types of free trade agreements play a role in guaranteeing and regulating the protection of economic rights of the community and domestic business actors amid the flow of global trade liberalisation. The findings indicate that multilateral treaties provide important global legitimacy and standards, while bilateral treaties allow for flexibility and protection of specific national issues. Synergy between the two is key to strengthening the sustainable protection of economic rights in Indonesia. This study provides recommendations for strengthening institutional capacity and stakeholder involvement in the implementation of agreements to achieve national economic justice and prosperity.